Analysis of the Effect of Learning Motivation on Learning Achievement - Anni Attika Robbi; Gusnardi Gusnardi; Sumarno Sumarno (Journal of Educational Sciences, 2020)
This study aims to determine how the influence of learning motivation on learning achievement. This research was conducted in class XII students majoring in Social Sciences at SMAN 2 Mandau, SMAN 8 Mandau, and SMAN 9 Mandau, Riau. The population consisted of 505 students and it was sampled as many as 224 students. This study was a descriptive quantitative study. Data were analyzed by simple linear regression method. The results of the study showed the learning motivation of class XII students at the Mandau District Public High School was included in the medium category. This was seen from the desire and willing of student to succeed in learning, the encouragement and need in learning, the hopes and ideals of the future, the appreciation of learning, the existence of interesting activities in learning and the existence of a conducive environment. Learning motivation has a significant effect on student achievement.